Professor Tim Congdon CBE - Phil Armstrong (Edward Elgar Publishing, 2020)
In a series of in-depth interviews with leading economists and policy-makers from different schools including Austrian, Monetarist, New-Keynesian, Post-Keynesian, Modern Monetary Theory, Marxist and Institutionalist, this intriguing book sheds light upon the behaviour of economists and the sociology of the economics profession by enabling economists to express their views on a wide range of issues.